Fish RIP1 Mediates Innate Antiviral Immune Responses Induced by SGIV and RGNNV Infection - Zhang, Xin; Liu, Zetian; Wu, Siting; Sun, Mengshi; Wei, Jingguang; Qin, Qiwei (Frontiers in Immunology, 2020)
Receptor interacting protein 1 (RIP1) is an essential sensor of cellular stress, which may respond to apoptosis or cell survival and participate in antiviral pathways. To investigate the roles of fish RIP1 in Singapore grouper iridovirus (SGIV) and red-spotted grouper nervous necrosis virus (RGNNV) infection, a RIP1 homolog from orange-spotted grouper (Epinephelus coioides) (EcRIP1) was cloned and characterized. EcRIP1 encoded a 679 amino acid protein that shares 83.28% identity with that of Perca flavescens and contained a homologous N-terminal kinase (S-TKc) domain, a RIP isotype interaction motif (RHIM), and a C-terminal domain (DD). EcRIP1 was predominantly detected in immune tissues, and its expression was induced by RGNNV or SGIV infection in vitro. Subcellular localization showed that EcRIP1 was distributed in the cytoplasm with point-like uniform and dot-like aggregation forms. Overexpression of EcRIP1 inhibited SGIV and RGNNV replication and positively regulated the expression levels of interferon (IFN) and IFN-stimulated genes and pro-inflammatory factors. EcRIP1 may interact with grouper tumor necrosis factor receptor type 1-associated DEATH domain protein (EcTRADD) to promote SGIV-induced apoptosis, and interact with grouper Toll/interleukin-1 receptor (TIR) domain containing adapter inducing interferon-β (EcTRIF) and participate in Myeloid Differentiation Factor 88 (MyD88)-independent toll-like receptor (TLR) signaling. EcRIP1 may also interact with grouper tumour necrosis factor receptor-associated factors (TRAFs) as intracellular linker proteins and mediate the signaling of various downstream signaling pathways, including NF-κB and IFN. These results suggest that EcRIP1 may inhibit SGIV and RGNNV infection by regulating apoptosis and various signaling molecules. Our study offers new insights into the regulatory mechanism of RIP1-related signaling, and provides a novel perspective on fish diseases mediated by RIP1.